Illuminated by Darkness: Two Symbolist Masterpieces - Magun, Artemy (Stasis, 2018)
The article is dedicated to the problem of negativity in modernist art. It ties together the substantive gloom of a modernist artwork with the catastrophes that happen at the level of its form. In this sense, there is a difference among the shock aesthetic of mass culture, the abstraction of avant-garde, and the ideological and figurative construction that is provided by a symbolist artwork. The article offers an apology of symbolism, primarily in plastic arts, and demonstrates its incessant influence.